Penerbitan Obligasi Negara Sebagai Alternatif Pendanaan Defisit APBN Indonesia - Ratna Wulandari; Ulil Farrohah; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Deficit funding for the State Revenue and Expenditure Budget (APBN) is an important challenge for the government in maintaining fiscal stability and supporting development policies. In order to find an effective funding alternative, the issuance of state bonds has become an option. This study aims to analyze the position of issuing state bonds as an alternative to funding the state budget deficit. This study uses a descriptive-analytical approach by collecting data from various related sources. The analysis was carried out through a literature review, data from the Indonesian Ministry of Finance, and regulations regarding the issuance of Government Bonds. The results of the study show that the issuance of state bonds has several benefits as an alternative to financing the state budget deficit, namely diversifying government funding sources, reducing dependence on tax revenues and other income, providing flexibility in the schedule of interest and principal payments, in accordance with the government's financial capacity, attracting investor participation. institutional and retail, increasing financial market liquidity. APBN Deficit Funding is dominated by State Bonds, which of course the issuance of state bonds as an instrument for funding the APBN deficit makes fiscal space narrow. When the space for fiscal movement becomes limited, it means that the government faces limitations in collecting revenue or in managing government spending.